Revenue diversification in higher education: the case of Portugal - Antunes, Tatyana Yuryevna Koryakina (2014)
Socio-economic changes, alterations in societal expectations and new public policies have put pressures on higher education public funding, bringing the issue of funding diversification to the forefront. Income diversification, namely, generation of funds from private, as well as from competitive public sources, has become increasingly important in European higher education due to a complex financial environment and perceived deficit of innovation transfer. Although there are numerous studies about changes in national funding systems and allocation mechanisms, few have focused on diversification of funding sources, especially in the European context, making Portugal no exception. Thus, this study aims at exploring income diversification at the institutional level and its influence on the internal organisational structures. For this purpose two Portuguese public universities were chosen as case studies. The empirical material was collected through semi-structured interviews with top management and middle management of each university and through documentary analysis. Data analysis demonstrated that both universities are in the process of institutionalizing and formalising practices of income diversification, notably by getting more professional in how they are dealing with external stakeholders, such as businesses, local community, and students. However, the study also revealed that there is no formal, organised strategy to deal with income diversification. In general, the universities are reacting to external demands rather than pro-actively exploring opportunities. In this respect, the analysis determined several factors that promote or inhibit income diversification activities. Quality and favourable organizational culture were named by the interviewees as the most relevant factors for successful income diversification. External factors such as legal arrangements and funding conditions were cited as major constraints. This research has also revealed that revenue diversification activities tend to develop along the continuum towards higher sophistication and systematisation of activities that are supported by a powerful infrastructure. Together with efforts at the institutional level, the role of government policies proves to be crucial in providing tools and incentives to higher education institutions and creating a harmonious higher education system.